Perceptions of Education Quality, Facilities, and Teaching Staff at the Faculty of Economics, University of Klabat - Toetik Wulyatiningsih (Jurnal Multidisiplin Madani, 2023)
This study evaluates the changes in perception regarding education quality, the availability of facility and faculty staff before and after student enters the UBS at Klabat University.  Using t-Test Paired two sample for Means shows the results for the variable education quality do not experience changes in perceptions in all student batches which are considered good, more over considered better in creating reliable human resources and the accreditation system.  For the availability of facility is considered sufficient by all batches with change in perception, which is first assessed good and then changed to be sufficient or not to experience a change in perception, namely this is considered sufficient before and after entering UBS especially for variable library/laboratory complete and modern teaching equipment.  While the teaching staff do not experience a change in perception in all student batches with good assessment and even better for broad lecturer knowledge